2006
DOI: 10.1007/s10888-005-9017-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing poverty and deprivation dynamics: Issues of reliability and validity

Abstract: deprivation, dynamic, latent class analysis, measurement error, poverty,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
2
34
1
Order By: Relevance
“…This result might be interpreted as a consequence of the personal living conditions of each type of poverty. Several authors have argued that people who suffer under a longer spell of income poverty will assure their living standard as long as financial savings are available (Mayer and Jencks 1989;Layte et al 2001;Whelan et al 2001Whelan et al , 2002aWhelan et al , b, 2003Whelan et al , 2004Whelan and Maitre 2006). If these resources are completely exhausted, then living standards will decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result might be interpreted as a consequence of the personal living conditions of each type of poverty. Several authors have argued that people who suffer under a longer spell of income poverty will assure their living standard as long as financial savings are available (Mayer and Jencks 1989;Layte et al 2001;Whelan et al 2001Whelan et al , 2002aWhelan et al , b, 2003Whelan et al , 2004Whelan and Maitre 2006). If these resources are completely exhausted, then living standards will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…These have consistently shown that income poverty is only weakly associated to an inadequate living standard, although income measures are considered as indirect determinants of people's living situation (Desai and Shah 1988;Mayer and Jencks 1989;Deleeck and van den Bosch 1992;Muffels et al 1992;Muffels 1993;Callan et al 1993;Delhausse et al 1993;Halleröd 1994Halleröd , 1995Nolan and Whelan 1996a, b;Kangas and Ritakallio 1998;Andress 1999;Lipsmeier 1999, 2000;Delhey 1999, 2001;Klocke 2000;Lipsmeier 2001;Andress et al 2001Andress et al , 2004Layte et al 2001;Whelan et al 2001Whelan et al , 2002bWhelan et al , 2003Whelan et al , 2004Bradshaw and Finch 2003;Jensen et al 2003Jensen et al , 2007Halleröd et al 2006;Boarini and d'Ercole 2006;Whelan and Maitre 2006). In this context, studies have shown that long-term income poverty contributes much more to an inadequate living standard than shorter periods, especially since other financial resources can supplement possible income losses in the short run (Mayer and Jencks 1989;Layte et al 2001;Whelan et al 2002aWhelan et al , b, 2003Whelan et al , 2004Whelan and Maitre 2006). These results are consistent with other studies, which have indicated that income is only one of several important factors such as property ownership, health, age, education, employment and marital status that contribute to individual's living standard …”
Section: Introductionmentioning
confidence: 99%
“…Since the total net yearly household income in the ECHP is provided with a time lag of one year, the household income is recalculated by combining income information measured in year T'1 (though referring to the current year T) with household composition information of the current year T (for a discussion, see Debels and Vandecasteele 2008). The recent literature on poverty measurement shows that there is reason to assume that there is an overestimation of poverty mobility rates due to measurement error (Rendtel et al 1998;Breen and Moisio 2004;Whelan and Maître 2006). Especially the number of poverty exits seems to be overestimated and this implies that the poverty length in this article would generally be underestimated.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the social inequality determinants are as expected. Note that we can assume that the social divisions according to gender, education level and social class would be more pronounced when measurement error was accounted for (see Whelan and Maître 2006).…”
mentioning
confidence: 99%
“…Recent work on measurement error suggests, however, that this characterization may be over-stated. When poverty is assessed using an approach that corrects for measurement error, it appears that the risk of exposure is less equitably distributed than initially thought, and mobility is less common (Breen and Moisio 2004;Moisio 2004;Rendtel et al 1998;Whelan and Maitre 2006). These findings on individual poverty dynamics within countries may, in turn, affect conclusions about economic well-being in comparative perspective, as well as estimates of how well social transfers protect individuals from serious want.…”
Section: Introductionmentioning
confidence: 99%